Pengaruh Substitusi Campuran Limbah Abu Sekam Padi dan Bottom Ash Terhadap Kuat Lentur dan Rembesan Air pada Pembuatan Genteng Beton - Dynanti, Putri (Civil Infrastructure Engineering and Architectural Design, 2024)
Indonesia’s environmental problems in agriculture and electric power generation led to using rice husk ash and bottom ash for roof construction materials such as concrete roof tiles. Concrete roof tiles in Indonesia are still one of the roof coverings that require high costs and have a heavy mass, the addition of rice husk ash and bottom ash which have pozzolanic content and have a small specific gravity is expect the SNI requirements qualify. The method of research is quantitative experimental by observing the effect of variables based on SNI. The composition of the concrete roof tile mixture is 1 cement: 3 sand : 0,35 water and the percentage of rice husk ash and bottom ash. Rice husk ash against sand: bottom ash against cement, A 0%: 0%, B 5% : 10%, C 2.5% : 10%, and D 5% : 7.5%. Quality test of rice husk ash and bottom ash for manufacturing concrete roof tiles based on SNI 0096:2007, are bending load test, water seepage test, water absorption test, quality of appearance, and size. The results of the average bending load test on A = 1446,19 N, B = 1622,58 N, C = 1559,67 N, and D = 1530,79 N. Results of water seepage test on A, B, C, and D is no water drops. Test result of water absorption on A = 8,376%, B = 6,265%, C = 5,200%, and D = 6,400%. In the conclusion rice husk ash and bottom ash can improve the value of bending load, reduce the water seepage, reduce water absorption and protect the environment by reduce the waste.